1997
DOI: 10.1097/00000539-199704000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Epinephrine Test Doses During Spinal Anesthesia in Volunteers

Abstract: Epinephrine test doses may be administered during combined spinal-epidural anesthesia to determine intravascular placement of epidural catheters. This study was designed to determine systolic blood pressure (SBP) and heart rate (HR) responses to intravenous injection of epinephrine (15 microg) during spinal anesthesia. Twelve volunteers received three spinal anesthetics (lidocaine 100 mg, tetracaine 15 mg, and bupivacaine 15 mg) in a randomized, double blind, cross-over fashion. Epinephrine was administered pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
4
2
Order By: Relevance
“…This differs from a report showing that spinal anesthesia reduces hemodynamic responses to IV epinephrine injection [12]. However, Liu et al reported that epinephrine injection is unlikely to reduce detection by positive SBP and HR criteria [12]. We believe that this discordance can be explained by methodological variations between these studies.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This differs from a report showing that spinal anesthesia reduces hemodynamic responses to IV epinephrine injection [12]. However, Liu et al reported that epinephrine injection is unlikely to reduce detection by positive SBP and HR criteria [12]. We believe that this discordance can be explained by methodological variations between these studies.…”
Section: Discussioncontrasting
confidence: 79%
“…The responses to the circulating adrenergic activity may not be affected by spinal block. This differs from a report showing that spinal anesthesia reduces hemodynamic responses to IV epinephrine injection [12]. However, Liu et al reported that epinephrine injection is unlikely to reduce detection by positive SBP and HR criteria [12].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The amplitude of an epinephrine response is attenuated by the following factors for HR: aging (18), previous administration of ␤-adrenergic blocking drugs (selective or nonselective) (15), the combination of midazolam (arousable by verbal command) and fentanyl (2 g/kg IV) (29), isoflurane (hemodynamic responses to intravascular injection of test doses vary with dose of epinephrine and depth of anesthesia) (30), sevoflurane (2% end-tidal concentration) (20), spinal blockade (31) or high (T 5 ) thoracic epidural anesthesia combined with general anesthesia (32) but not by IV atropine (administered just before the test dose) (33), midazolam alone (29), oral clonidine (24), or low (T 10 ) thoracic epidural anesthesia (32). The increase in SBP is affected by isoflurane (30), spinal (31) or high thoracic (T 5 ) epidural anesthesia (32) but not by aging (18,34), ␤-adrenergic blocking drugs (15), the combination of midazolam and fentanyl (29), oral clonidine (24), sevoflurane (20), or low (T 10 ) thoracic epidural anesthesia (32).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in SBP is affected by isoflurane (30), spinal (31) or high thoracic (T 5 ) epidural anesthesia (32) but not by aging (18,34), ␤-adrenergic blocking drugs (15), the combination of midazolam and fentanyl (29), oral clonidine (24), sevoflurane (20), or low (T 10 ) thoracic epidural anesthesia (32). The T wave amplitude decrease is not affected by the combination of midazolam and fentanyl (29), sevoflurane anesthesia (21), or the electrocardiogram lead (I, II, III, or V (5)) monitored (35).…”
Section: Resultsmentioning
confidence: 99%